Use of mobile telemedicine for cervical cancer screening - Quinley, Kelly E (2011)
Visual inspection of the cervix with application of 4% acetic acid (VIA) is an inexpensive alternative to cytology-based screening in areas where resources are limited, such as in many developing countries. We have examined the diagnostic agreement between off-site (remote) expert diagnosis using photographs of the cervix (photographic inspection with acetic acid, PIA) and in-person VIA. The images for remote evaluation were taken with a mobile phone and transmitted by MMS. The study population consisted of 95 HIV-positive women in Gaborone, Botswana. An expert gynaecologist made a definitive positive or negative reading on the PIA results of 64 out of the 95 women whose PIA images were also read by the nurse midwives. The remaining 31 PIA images were deemed insufficient in quality for a reading by the expert gynaecologist. The positive nurse PIA readings were concordant with the positive expert PIA readings in 82% of cases, and the negative PIA readings between the two groups were fully concordant in 89% of cases. These results suggest that mobile telemedicine may be useful to improve access of women in remote areas to cervical cancer screening utilizing the VIA `see-and-treat' method.